Flexible piezoelectric nanocomposites based on PVDF-HFP/PLA blend doped PZT - Oumghar, K; Chakhchaoui, N; Eddiai, A; Cherkaoui, O; Mazroui, M (IOP conference series. Materials Science and Engineering, 2023)
In the present work, we studied the effect of adding PZT nanoparticles to PVDF-HFP/PLA matrix on piezoelectric properties of blend-based nanocomposites. Polyvinylidene fluoride hexafluoro-propylene /Polylactic acid /Lead titanate zirconate (PVdF-HFP/PLA/PZT) films nanocomposites were prepared by solvent casting technique using different percentages of PZT Nano fillers. The different samples were characterized by Polarized optical microscope (POM), Fourier transformed infrared (FTIR) and Thermogravimetric analysis (TGA). POM images indicate uniform distribution of PZT Nano fillers in the PVdF-HFP/PLA matrix. FTIR analysis reveals the appearance of β-phase in nanocomposites and the enhancement of their piezoelectric properties. These electroactive nanocomposites thin films are a potential candidate for the piezoelectric Nano generators, energy storage devices and energy harvesting applications.